2011
DOI: 10.1007/s13253-011-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Model for Presence-Only Semicontinuous Data, With Application to Prediction of Abundance of Taxus Baccata in Two Italian Regions

Abstract: In studies about the potential distribution of ecological niches, only the presence of the species of interest is usually recorded. Pseudo-absences are sampled from the study area in order to avoid biased estimates and predictions. For cases in which, instead of the mere presence, a continuous abundance index is recorded, we derive a two-part model for semicontinuous (i.e., positive with excess zeros) data which explicitly takes into account uncertainty about the sampled zeros. Our model is a direct extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
8
0
4
Order By: Relevance
“…Bayesian approaches (Eddy, 2004) incorporating collection activity in species distribution model estimates have also been investigated. Latimer et al (2006) and Royle et al (2007) demonstrated a hierarchical framework incorporating spatially explicit details such as the complexity of irregular sampling intensity (termed 'spatial coverage bias' by Royle et al, 2007) (see also Gelfand et al, 2003;Arg aez et al, 2005;Latimer et al, 2006;Ward et al, 2009;Di Lorenzo et al, 2011;Hui et al, 2011;Golini, 2012). Bias correction features are available in Maxent, the widely used, machine learning approach to species distribution modelling that uses presence/background data to generate model estimates (Dud ık et al, , 2007Phillips et al, 2004Phillips et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian approaches (Eddy, 2004) incorporating collection activity in species distribution model estimates have also been investigated. Latimer et al (2006) and Royle et al (2007) demonstrated a hierarchical framework incorporating spatially explicit details such as the complexity of irregular sampling intensity (termed 'spatial coverage bias' by Royle et al, 2007) (see also Gelfand et al, 2003;Arg aez et al, 2005;Latimer et al, 2006;Ward et al, 2009;Di Lorenzo et al, 2011;Hui et al, 2011;Golini, 2012). Bias correction features are available in Maxent, the widely used, machine learning approach to species distribution modelling that uses presence/background data to generate model estimates (Dud ık et al, , 2007Phillips et al, 2004Phillips et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, if the false absences occur randomly in space (no preferential sampling), several methods are available (Ward et al . ; Warton & Shepherd ; Di Lorenzo & Farcomeni ) in addition to BIR. In this context, there is currently a debate regarding whether the probability of occurrence can be inferred from presence‐only data sets.…”
Section: Discussionmentioning
confidence: 99%
“…(). These kind of data are now common in ecology (Scarnati et al., ; Di Lorenzo et al., ; and references therein) and the focus may be on prediction, interpretation, or both. In fact, researchers are usually interested in predicting an area of suitability for each species of interest, or to relate the abundance with predictors such as level of humidity, median temperature in the summer, etc.…”
Section: Application To Ecological Niches Of South Africamentioning
confidence: 99%
“…More details on the measurements in the NIAPS, which were later converted to abundance measures and linked by us to environmental covariates, can be obtained from Kotzé et al (2010). These kind of data are now common in ecology (Scarnati et al, 2009;Di Lorenzo et al, 2011;and references 167 .144 .239 .290 .886 .988 .163 .165 .219 .214 .829 .952 .156 .146 .189 .197 .760 .874 .143 .094 .162 .121 .615 .643 therein) and the focus may be on prediction, interpretation, or both. In fact, researchers are usually interested in predicting an area of suitability for each species of interest, or to relate the abundance with predictors such as level of humidity, median temperature in the summer, etc.…”
Section: Application To Ecological Niches Of South Africamentioning
confidence: 99%